Utilizing Four Square Method (FSM) to Enhance Students’ Speaking Ability - Sofyan Sukwara Akfan (Hasanuddin University, 2018)
This research conducted with the consideration that speaking ability can be enhanced with the implementation of Four Square Method This research was attended to find out the extent to which utilizing Four Square Method in teaching speaking will enhance students’ speaking skill or not and to investigate students’ perception in utilizing Four Square Method in enhancing their speaking ability. The researcher used a quasi-experimental design involved two groups, they are: an experimental group that used Four Square Method while control group that used traditional method. The data of pre-test and post-test were analyzed by two independent raters by refering to Heaton’s speaking band score; while the students perception toward the implementation of Four Square Method was analyzed by using Likert's ’cale. There were 60 participants in this research where 30 in the experimental group and 30 in the control group. They were second grade students of SMAN 1 Baubau. The instruments used were speaking test, questionnaire and recorder. After the data analyzed, the researcher lounched that there is a significant enhancement of students’ speaking ability as the mean score of experimental group (accuracy: pre-test 2.80 and post-test 4.07), control group (accuracy: pre-test 3.73 and post-test 3.67). Experimental group (fluency: pres-test 2.70 and post-test 4.10), control group (fluency: pre-test 4.03 and post-test 3.57). Experimental group (comprehensibility: pre-test 2,63 and post-test 3,93) while control group (comprehensibility: pre-test 3.57 and post-test 3.73) and experimental group (content: pre-test 2.87 and post-test 4.43) while control group (content: pre-test 4.13 and post-test 4.40). Students’ perception toward the implementation of Four Square Method (FSM) was positive; 66.7% from the students (20) had high interest and 33.3% (10 students) categorized as moderate. It declares that Four Square Method is effective in enhancing student’s speaking ability.